Amnestic mild cognitive impairment in elderly of a health area - Yordanis Garbey Pierre; Marlene Marina Gorguet Pi; Yudit Batista Delgado; Maite Gonzalez Ramos (Centro Provincial de Información de Ciencias Médicas, 2023)
Introduction: Age is the most important risk factor associated with cognitive deterioration. In this regard, loss of memory is a frequent and growing reason for attention in medical consultations of primary care. However, cognitive dysfunction in the elderly is one of the affections that usually go without an opportune diagnosis. Objective: To determine the prevalence of the amnestic mild cognitive impairment in elderly of a health area. Methods: An observational, descriptive and cross-sectional study of 203 elderly, belonging to the health area of Ramón López Peña Teaching Polyclinic was carried out in Santiago de Cuba, from June to December, 2022. To diagnose the patients with light cognitive dysfunction the Petersen approaches were used. Results: It was found that 36.9% of the elderly presented amnestic mild cognitive impairment, with a prevalence of male sex (43.6%) and the primary school level (50.0%), followed by the middle level (40.3%). Conclusions: Amnestic mild cognitive impairment prevailed in more than a third of the studied sample; frequency that increased according to the age. Likewise, a higher incidence of male sex and the elderly with concluded primary and middle schooling was detected.